A CASE STUDY: PARENTS’ PERCEPTIONS ON CHILDREN BILINGUAL EDUCATION IN BALI - Pratama, Pande Gede Artha (Universitas Pendidikan Ganesha, 2017)
This article aimed to discuss the parents’ perceptions, on children bilingual education in Bali. Bilingual education could be defined as involving or using two languages in education system, in which one of the language used is students’ native language and in using the languages without mentioning the degree of each language proportion. This small investigation explored a young Balinese girl who became bilingual in English and Bahasa Indonesia and her parents’ perceptions about bilingual education. It involved participant observation, questionnaires administer and interview with her parents. The results of the study showed that the parents wanted their children to be bilingual because it would help in getting better life. Besides, collaboration between teachers, parents, society and environment is needed in order to promote bilingual education without losing children native language, because the parents believe that being bilingual meant children can speak both foreign language and native language equally without losing their native language